Structural reliability assessment of container ship at the time of accident. (May 2015) - Parunov, Josko; Andric, Jerolim; Corak, Maro; Kitarovic, Stanislav
Hull girder reliability assessment of the MSC Napoli at the time of accident is presented. Loads considered in the study are still water bending moments, vertical wave bending moments and whipping bending moments, while structural capacity is represented by the hull girder ultimate strength. Load combination between wave and whipping bending moments is considered. The probability of failure is calculated using a first-order reliability method. Sensitivity study is performed in order to investigate influence of the pertinent random variables. The uncertainty model of the basic random variables involved is consistent with the recent proposal by the International Maritime Organization, thus enabling direct comparison of the obtained results with reliability levels proposed by International Maritime Organization.